Quality of Life in The Elderly Viewed from Hope, Friend Support, and Family Support - I Ketut Andika Priastana; Dwi Prima Hanis Kusumaningtiyas (Universitas STRADA Indonesia, 2020)
The population in this study is the elderly who live in Banjar Tengah, Negara District, Jembrana Regency, Bali. The sample used in this study was selected using purposive sampling method, with a total sample of 62 people who met the criteria. The results showed that there was a significant effect simultaneously of hope, support from friends, and family support on the quality of life of the elderly because the p value Chi-Square was 0,000 where <α 0.05 or the value of Chi-Square Count 70.870> Chi-Square table. 7,815. The logistic regression test results show that the Nagelkerke R Square value is 0.908 and Cox & Snell R Square is 0.681, which indicates that the ability of the independent variable to explain the dependent variable is 0.908 or 90.8% and there are 100% - 90.8% = 9,2% other factors outside the model that explain the dependent variable